Press freedom and corruption in third world countries (2009)
The age-long endemic issue of corruption has been a global menace. However, its multifarious consequences have greater negative impact on the third-world/developing countries in contradistinction to the developed world. This study focuses on press freedom as a panacea to the endemic Problem of corruption among other preventive measures particularly as it affects the developing economies using cross country data. For this, more than 15 developing countries are analyzed. Emphasis is placed on both the private and public sectors of the understudied nations. The empirical findings of the study reveal that there is high incidence of corruption in developing economies with less or no tolerance for press freedom. The upshot of the study is that the governments of the developing countries should focus more on press freedom as a catalyst for curtailing the high level of corruption.